Etapele formării legislaţiei ecologice în Republica Moldova: aspecte istorice - Guceac, Ion; Ursu, Victor (My University, 2007)
It is also an axiom that ecology is considered not only as a science, doctrine or concept, but also a very old law source, since it is the law that led relations between human and environment. Norms that are regulating human-nature relations have their sources in different old texts. These texts referred to national protection and appropriation of hunting, fishing, fire protection, and collective protection against natural phenomena. Thus, the old Moldavian law contained a number of rules and institutions concerning average protection of such factors as forest, water, soil, hunting, fishing, etc. In this work the authors will try to systematize formation periods of ecological law in Republic of Moldova, classifying it in three stages. Concomitantly, one tries to analyze these stages in different periods of time, and developing level of ecological legislation.